Pengaruh modal kerja terhadap profitabilitas pada perusahaan go publik di bursa efek indonesia tahun 2017-2021 - Rahayu, Nofa Asmi; Chairiyaton, Chairiyaton (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Net profit is an illustration of the success of a company in managing its working capital. In its management, it can be seen as a form of whether or not the use of working capital in the company is effective. The purpose of this study was to determine the effect of working capital on profitability in companies that went public on the Indonesia Stock Exchange. Case study at (PT. Bank Syariah Indonesia). In this case the variables used are Working Capital Turnover, Accounts Receivable Turnover, and Cash Turnover. The sample used is data obtained from the Annual Financial Report of PT. Indonesian Islamic Bank. For 5 Years (2017-2021). The test results from this study first obtained a result of 0.161, it was concluded that working capital turnover had no significant effect on profitability. Furthermore, the second test results obtained that is equal to 0.831 so that it can be concluded that Accounts Receivable Turnover has no significant effect on Profitability. Then the third test results obtained results of 0.165 thus concluded that Cash Turnover has no significant effect on profitability.